Managing the Process of Cognitive Activity Development in Students of Pedagogic Specialties in Higher Education - Stukalenko, Nina Mikhailovna; Menlibekova, Gulbakhyt Zholdasbekovna; Anarbek, Nazgul; Abalakova, Balym Tyulegazinovna (International Review of Management and Marketing, 2016)
One of the significant problems in theory and practice of education management is managing the process of cognitive activity development in prospective specialists in the conditions of professional education. Various social and economic changes, which are currently happening in all of the life areas, stimulate human activity. Because of this, we are faced with the need to prepare pedagogic specialists, who can meet the current requirements that orient education system on the cognitive activity development, because the education has to provide successful personality integration in the world culture. Cognitive activity development is one of the priority directions in the present education system, which allows the college students to navigate in their future professional activity quickly and correctly and to flexibly adapt in the world of science and the new education system. Due to this, the system of higher professional education requires the development of conditions for managing the process of cognitive activity development in prospective teachers. Keywords: education management, managing the education, higher education, professional education, cognitive activity, cognitive interest. JEL Classifications: I210, I280, Z180